2015
DOI: 10.1152/ajpendo.00093.2015
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ controls pregnancy outcome through activation of EG-VEGF: new insights into the mechanism of placental development

Abstract: QY, Congiu C, Onnis V, Benharouga M, Feige JJ, Alfaidy N. PPAR␥ controls pregnancy outcome through activation of EG-VEGF: new insights into the mechanism of placental development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…5,29 Altogether our findings have demonstrated that EG-VEGF induces a PIH phenotype if maintained beyond the first trimester of pregnancy and provides evidence to suggest that maintenance of elevated EG-VEGF during the second and third trimesters of pregnancy contributes to the attenuation of this pathogenesis. These in vivo observations are consistent with our previous studies using human tissues during normal pregnancy 11,16,31,32 and also in pathological pregnancies. 9,12,13 Therefore, this study provides novel insights into the fine role of EG-VEGF in the development of PIH and the attenuation of its pathological symptoms, once the pathology is established.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5,29 Altogether our findings have demonstrated that EG-VEGF induces a PIH phenotype if maintained beyond the first trimester of pregnancy and provides evidence to suggest that maintenance of elevated EG-VEGF during the second and third trimesters of pregnancy contributes to the attenuation of this pathogenesis. These in vivo observations are consistent with our previous studies using human tissues during normal pregnancy 11,16,31,32 and also in pathological pregnancies. 9,12,13 Therefore, this study provides novel insights into the fine role of EG-VEGF in the development of PIH and the attenuation of its pathological symptoms, once the pathology is established.…”
Section: Discussionsupporting
confidence: 93%
“…We used murine sFlt1 (RayBiotech, Le Perray-en-Yvelines, France), murine sEndoglin (R&D systems, Lille, France), and human EG-VEGF 12,16,17 (PeproTech, Neuilly-surSeine, France) commercial assay kits. For each assay, 2 separate standard curves were constructed to allow accurate readings of samples at upper and lower ranges of the assay.…”
Section: Blood Pressurementioning
confidence: 99%
“…PPAR-γ is involved in trophoblast differentiation and also in the invasion of extravillous trophoblasts and differentiation of villous trophoblasts into [18][19][20]. In addition, PPAR-γ regulates the production and secretion of human chorionic gonadotropin (hCG) and vascular endothelial growth factor (VEGF) in the placenta as well as being involved in placental lipid transport and homeostasis [18,19,21,22]. Furthermore, PPAR-γ is involved in regulating the oxidative stress response, angiogenesis, hypertension as well as exerting anti-inflammatory effects during pregnancy [23][24][25], by regulating various gene targets such as interleukin-6 (IL6), tumor necrosis factor α (TNF), heme-oxygenase-1 (HMOX1), leptin and mucin-1 (MUC1) [26][27][28][29].…”
mentioning
confidence: 99%
“…PROKR1 and PROKR2 are highly expressed in villous cytotrophoblasts (VCT) as well as micro-and macrovascular placental endothelial cells (Brouillet et al, 2010). At the cellular level, EG-VEGF is expressed in the syncytiotrophoblast (ST), VCT, fetal endothelium, and Hofbauer cells (Ho) (Hoffmann et al, 2006;Holloway et al, 2014;Garnier et al, 2015). Lang et al (2003) reported distinct morphogenetic, antigenic and functional differences between the two EC types present in the placenta, with respect to the secretion of vasoactive substances and the proliferative response to cytokines.…”
Section: Prokineticin Family In the Control Of Placental Angiogenesismentioning
confidence: 99%
“…Since its identification EG-VEGF has been associated with the control of placental angiogenesis during the first trimester of pregnancy and the reactivation of its receptors in the placenta of patients with pregnancy pathologies such as PE and FGR (Brouillet et al, 2010(Brouillet et al, , 2012a(Brouillet et al, , 2013a(Brouillet et al, , 2014aGarnier et al, 2015;Alfaidy, 2016;Sergent et al, 2016). The reactivation of angiogenic processes was meant to compensate for the associated deleterious vascularization.…”
Section: Key Regulators Of Prokineticins For Successful Placental Angmentioning
confidence: 99%